Value Coalition Sebagai Strategi Pengembangan BUMDesa Pertanian - Nur Ariyanto; Muhammad Fazri; Farida Yustina; Arif Purbantara (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Gajah District is one of the centers of food crops in Demak Regency, but not a single agricultural BUMDesa grew in Gajah District until the end of 2019. Only a few researchers have used the value chain, and value coalition approaches in mapping potential business fields and forms of collaboration between BUMDesa-based agriculture. This study aims to formulate an agriculture-based BUMDesa development strategy through a value chain and coalition approach in Gajah District, Demak Regency. Data was collected through in-depth interviews, observation, and Focus Group Discussion (FGD). Value chain analysis is used to map alternative BUMDesa business fields. SWOT analysis with a value coalition approach is used to answer the development strategy. Selection of research locations based on Hierarchical Cluster Analysis. The suggested development of agriculture-based BUM Desa in Gajah District, Demak Regency is to follow the value coalitions process as follows: BUM Desa Kedondong focuses its business on agriculture machine rental services (rice transplanter, hand tractors, and combined harvesters), BUM Desa Mlatiharjo plays the role of superior provider seeds, BUM Desa Tambirejo as distributors of production inputs (fertilizers, pesticides, agricultural inputs), while BUM Desa Banjarsari is engaged in rice milling and warehousing.